Development And Characterization Of Yogurt Like Probiotic Product From Jackfruit (Artocarpus Heterophyllus) Seed Milk - Kamaruzzaman, Noor Qamarina (Universiti Sains Malaysia, 2020)
The potential of converting the jackfruit wastes (peels and seeds) which may cause serious waste discarding including environmental problems, into an improved product is being studied due to an abundant amount of those inedible parts. Utilisation of jackfruit seeds and soybeans as the main ingredients for yogurt making is an approach to give added value and commercialising jackfruit seeds. Initially, yogurt with different ratio of milk from both jackfruit seed and soymilk were prepared based on the fixed ratio; 100% jackfruit seed milk (J100), 100% soymilk (S100) and 50% jackfruit seed milk with 50% soymilk (JS50). Physical measures were conducted on the developed yogurt in terms of colour, viscosity, syneresis, titratable acidity and pH measurement. An increase in the percentage of jackfruit seed milk shown significant impact on the physical properties whereby viscosity value increased, while syneresis was decreased and titratable acidity became the lowest. The probiotic count on different concentration of jackfruit seed milk and soymilk in the developed yogurt did not vary significantly due to the constant amount of starter culture used. Different concentration of jackfruit seed milk and soymilk in yogurt samples shown significant impact on the ash, protein, fat, and carbohydrate estimation. Developed yogurt from 100% soymilk showed more yellowish colour while, 100% jackfruit seeds milk develop a light brown colour compared to the other yogurt samples. Therefore, it can be concluded that the range of different percentage of both jackfruit seed milk and soymilk in the yogurt samples influenced the physicochemical properties (physical, microbial, and proximate analysis) compared to the commercial one.